ANALISIS PENGARUH RETURN ON ASSETS (ROA), LOAN TO DEPOSIT RATIO (LDR), DAN NON PERFORMING LOAN (NPL) TERHADAP PRICE EARNING RATIO (PER) PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2011 - 2014 - ADE IRAWAN (Pekobis : Jurnal Pendidikan, Ekonomi, dan Bisnis, 2018)
ABSTRAK This  research was conducted to examine the effect of Return On Assets (ROA), Loan to Deposit Ratio (LDR), and Non-Performing Loans (NPL) to Price Earning Ratio (PER). The research sample was taken from 23 commercial banks listed company in Indonesia Stock Exchange that have gone through a screening process to obtain a representative sample in accordance with the criteria of samples or known by purposive sampling method. Methods of data analysis used in this study is the method of analysis using Eviews 7.1 Panel Data. These results indicate partial ROA has a negative and significant effect on the PER of 49.72%, LDR has no real effect, and no significant effect on the PER, NPL has a real and significant effect on the PER of 38.40%. While simultaneously PER, LDR , and NPL together (simultaneously ) had no significant effect on the PER Kata Kunci: Return On Assets, Loan to Deposit Ratio, Non Performing Loan, Price Earning Ratio, Purposive Sampling, Eviews